Bullying and Adjustment Problems in Islamic Elementary School - Erni Agustina Setiowati (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2017)
The number of bullying cases is getting more significant among students. The effect of bullying covers some conditions of psychology, physic, and adjustment either for bullies, bully-victims or whoever witnesses the action (bystander). The cases of bullying more problematic if the action occurs in Islamic-based schools. In the Holy Quran, there are 12 verses which correlate to enmity (i’tada ya’tadi). Besides, it also has 39 verses about scolding (istahzaa yastahziu). Thus, actions relating to harassment should be decreased more than non-Islamic-based schools. This study aims to describe bullying behavior and adjustment. The quantitative method is used for this study. The sample involved in this study was 73 students of Islamic elementary schools in the district of Semarang Utara selected by purposive sampling. The data were collected through a questionnaire of bullying behavior, reliability coefficient α=0.890 and corrected correlation coefficients was in the range between 0.268-0.552. SCT (Sentence Completion Test) for Children was used to measure the perception of adjustment problems. Data was analyzed by a descriptive statistic. The finding indicated that bullying was in a high category and students have some adjustment problems related to interpersonal relationships, in school and family, and self-concept.